2013
DOI: 10.2214/ajr.12.9453
|View full text |Cite
|
Sign up to set email alerts
|

Stenosis Quantification of Coronary Arteries in Coronary Vessel Phantoms With Second-Generation Dual-Source CT: Influence of Measurement Parameters and Limitations

Abstract: The results are an overview of factors that influence stenosis quantification in simulated coronary arteries. Dual-source CT is highly reproducible and accurate for quantification of low-density stenosis in vessels with a diameter of 3 mm and attenuation of at least 200 HU for different degrees of stenosis and plaque geometry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 33 publications
0
21
0
Order By: Relevance
“…The results demonstrated that smaller areas and diameters had greater degrees of error in comparison to larger areas and diameters. For example, a 0.20 mm 2 area with a 0.5 mm diameter had a difference error of 664% from its true size, while a 12.57 mm 2 area with a 4 mm diameter had a difference error of 17% …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The results demonstrated that smaller areas and diameters had greater degrees of error in comparison to larger areas and diameters. For example, a 0.20 mm 2 area with a 0.5 mm diameter had a difference error of 664% from its true size, while a 12.57 mm 2 area with a 4 mm diameter had a difference error of 17% …”
Section: Resultsmentioning
confidence: 99%
“…The resolution is expressed in dots per inch (dpi) or micrometers (lm) and assessed by comparing the dimensions of the produced physical phantom with the original dimensions provided to the printer. Among the papers used, 10 have assessed the resolution or accuracy of the printer by quantitative (numerical) comparison, [26][27][28][29][30][31][32][33][34][35] 10 by qualitative (figural) comparison, 22,[36][37][38][39][40][41][42][43][44] and 14 by both quantitative and qualitative comparison. 10,21,[45][46][47][48][49][50][51][52][53][54][55][56] Sixteen of the research articles do not include a verification of the printers' resolutions.…”
Section: A Characterization Of 3d-printed Phantom Spatial Accuracymentioning
confidence: 99%
See 1 more Smart Citation
“…These phantoms can be created using 3D printing, a technique with applications in different imaging modalities, including CT, for imaging and dosimetry purposes. [26][27][28][29][30][31] In this work, a 3D printed phantom with vessel-like structures designed in a similar way to the lung was used to validate the proposed method for quantifying vessel morphology. A sufficiently high-resolution micro-CT scan of the lung phantom was acquired and used as the ground truth for the vessel distribution.…”
Section: Introductionmentioning
confidence: 99%
“…Polymers and various polymeric composites have been commonly utilized as computed tomography (CT) phantoms due to their manufacturability and potential for wide ranged material properties. [1][2][3][4][5] However, current phantom devices are specific to the desired tissue whereas some studies aiming to improve CT medical imaging necessitate the control of the phantom CT characteristics to a fine degree. 6,7 Certain tissues and structures within the human body may differ and require a fine degree of CT number control to be anthropomorphic.…”
Section: Introductionmentioning
confidence: 99%